Menakar Resiko Pembangunan Prototipe User Experience Dengan Weighted Risk Check List - Wira Munggana (Universitas Multimedia Nusantara, 2015)
Development of User Experience (UX) artifacts such as annotated wireframes, immersive prototypes, and detailed documentation should be done by a UX designer specialist, however most of them are not programmers. It can be done by using UX designer tools widely available today. Aside from what tools they used, this paper higlights forecasting the risk of an UX prototype project using weighted risk check list. Index Terms - Heuristic, User Interface Design, User Experience Prototype, Weighted Risk Check List, Wireframe.